Moisture-curing reactive hot melt adhesive for flocking weather strips, weather strips with flocking and manufacturing method thereof
Patent Information
- Application Number
- JP2020143070
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-08-27
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2040-08-27
AI Technical Summary
【0016】 冷却固化したばかりの接着剤は湿気硬化による高分子量架橋に伴う強靭性が十分に発現していない為、曲げ応力に対してひび割れが生じ易いが、本発明の接着剤は、25℃の貯蔵弾性率が2.85×108Pa以下のウレタンプレポリマーを用いているため、曲げ応力を掛けてもひび割れが生じることがなく、速やかに後加工処理を行うことが可能で、生産性を向上させるものである。
Smart Images

Figure 0007647033000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a moisture-curing reactive hot melt adhesive for flocking weatherstrips, a flocked weatherstrip, and a method for producing the same. The weatherstrip of the present invention has flocking on the sliding surface with glass or the like, and is particularly suitable for use in automobiles. [Background technology]
[0002] 2. Description of the Related Art Weatherstrips having a sliding surface that comes into contact with glass are commonly provided with flocking on the sliding surface in order to reduce sliding resistance and ensure sealing performance.
[0003] There are two types of adhesives used for flocking: emulsion type and solvent type. However, the adhesives used for weather stripping are generally two-component solvent type or one-component solvent type, as they are intended to provide adhesion to the base material and water resistance.
[0004] Conventional manufacturing methods for flocked weatherstrips using these adhesives involve applying a prescribed thickness of adhesive to the sliding surface of the weatherstrip, electrostatically flocking the pile, cutting the weatherstrip to a prescribed size while the cut edges are clamped together, and then heating is performed to dry the solvent and harden the adhesive. Finally, both ends of the weatherstrip that have been deformed by being clamped during cutting and have poor pileability are cut off.
[0005] The reason for cutting before drying is to reduce the drying space required, that is, if it takes about 10 minutes to dry, and the line speed is 10 m / min, for example, a drying oven length of 100 m is required, which requires a large space. Usually, a drying line runs perpendicular to the flocking line, with a width that allows the transport of flocked weather strips cut to a specified size.
[0006] Japanese Patent Application Laid-Open No. 5-96670 discloses a flocked material in which pile is electrostatically flocked to a substrate via an adhesive made of a urethane prepolymer, but the crystallinity of the urethane prepolymer described in this publication is unclear.
[0007] When using the above-mentioned solvent-type adhesive, both ends of the cut part are clamped before drying, so it is necessary to cut and discard the deformed ends that occur during cutting, but the amount of waste is about 10% of the total. Therefore, there is a loss of about 10% in variable costs and processing fees, and unnecessary waste is generated.
[0008] In addition, the use of solvents can lead to problems such as a worsening working environment and the risk of fire, and drying them requires a large amount of energy costs. Furthermore, in the case of two-liquid systems, there is the problem of poor curing due to incorrect mixing of the hardener.
[0009] Adhesive compositions for use in flocking weather strips that solve the above problems are disclosed in Patent Documents 1 and 2.
[0010] The inventions described in these documents are moisture-curing reactive hot melt adhesives for flocking weatherstrips, characterized in that the main component is an isocyanate group-containing urethane prepolymer and the melting point is 40°C or higher and 150°C or lower. This hot melt adhesive allows the pile, which is implanted in a molten state, to be firmly fixed to the weather strip base material in a short time, and since the pile has sufficient standing strength after implantation, it is not deformed by pinching stress when cut. This eliminates the loss and waste that occurs when using solvent-type adhesives. In addition, since it is solvent-free, there is no deterioration of the working environment or the risk of fire, and since it does not require a drying process, energy costs can be reduced. Furthermore, since it is a one-component type, there is no need to worry about mixing the hardener, which is a problem with two-component solvent-type adhesives.
[0011] However, in the manufacturing process of weatherstrips in which this hot melt adhesive is used to electrostatically flock a weatherstrip substrate, the pile after flocking is cut to a specified length, and the bending stress generated during the subsequent processing steps can cause cracks in the hot melt adhesive layer after cooling and solidifying. In order to prevent this cracking, it is necessary to wait until the post-processing is completed to develop the toughness associated with high molecular weight crosslinking due to moisture curing, which can reduce productivity. [Prior art documents] [Patent documents]
[0012] [Patent Document 1] JP 2002-38120 A [Patent Document 2] JP 2002-224612 A Summary of the Invention [Problem to be solved by the invention]
[0013] The present invention provides a hot melt adhesive and flocked weatherstrip that improves the cracking of the adhesive layer caused by bending stress that occurs during post-processing of the weatherstrip cut to a specified length after flocking in a manufacturing process in which electrostatic flocking is performed on a weatherstrip using a hot melt adhesive made of a urethane prepolymer, as well as a highly productive manufacturing method for flocked weatherstrips. [Means for solving the problem]
[0014] The inventors conducted extensive research to solve this problem and discovered that a hot melt adhesive that has just cooled and solidified does not exhibit the toughness associated with high molecular weight crosslinking due to moisture curing, and is therefore prone to cracking when subjected to bending stress; and that by adjusting the hot melt adhesive to consist of a urethane prepolymer having a storage modulus at 25°C within a specific range, it is possible to obtain a property that prevents cracking even when a bending stress is applied to the adhesive immediately after cooling and solidifying.
[0015] Means for solving the above problems include the following aspects. <1> The main component is an isocyanate group-containing urethane prepolymer, the melting point is 40°C or higher and 150°C or lower, and the storage modulus at 25°C before moisture curing is 2.85 x 10 8 A moisture-curing reactive hot melt adhesive for flocking weatherstrips, characterized by a compressive strength of 100 Pa or less. <2> It is characterized by a bending fracture strain of 1.7% or more at 25°C before moisture curing. <1> 2. The moisture-curing reactive hot melt adhesive for flocking weatherstrips according to claim 1 . <3> It is characterized by having a relative dielectric constant of 3 or more and 10 or less at 25°C. <1> or <2> 2. The moisture-curing reactive hot melt adhesive for flocking weatherstrips according to claim 1 . <4> The tack-free time measured by the following test method is within 10 minutes. <1> ~ <3> The moisture-curable reactive hot melt adhesive for flocking weather strips according to any one of the above. (Test method): The adhesive is heated to 120±5°C and melted, and applied uniformly to a 1cm x 1cm square with a thickness of 100±10μm on a 100μm thick polyethylene terephthalate film, and then immediately placed in a thermostatic chamber maintained at 25±1°C. The applied surface is then touched with a finger to measure the time it takes for the adhesive to lose its tackiness. <5> The tack-free time is between 30 seconds and 4 minutes. <4> 2. The moisture-curing reactive hot melt adhesive for flocking weatherstrips according to claim 1 . <6> It is characterized by a melt viscosity of 1000 to 50000 mPa·s / 120°C. <1> ~ <5> The moisture-curable reactive hot melt adhesive for flocking weather strips according to any one of the above. <7> <1> ~ <6> A weather strip with flocking, comprising a substrate and flocking thereon via the moisture-curable reactive hot melt adhesive for flocking weather strips according to any one of claims 1 to 5. <8> <1> ~ <6> a moisture-curable reactive hot melt adhesive for flocking weatherstrips according to any one of the above, which is applied to a substrate in a thickness of 40 to 150 μm by heating and melting the adhesive; electrostatically flocking pile fibers onto the substrate surface; cooling and solidifying the adhesive to bond the pile fibers to the substrate; and cutting the substrate to a predetermined size. Effect of the Invention
[0016] An adhesive that has just cooled and solidified does not fully exhibit the toughness associated with the high molecular weight crosslinking caused by moisture curing, and is therefore prone to cracking due to bending stress. However, the adhesive of the present invention has a storage modulus at 25°C of 2.85 x 10 8 Because it uses a urethane prepolymer with a strength of less than 1 Pa, cracks do not occur even when bending stress is applied, and post-processing can be performed quickly, improving productivity. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] 1. Glue The adhesive in the present invention is a moisture-curable reactive hot melt adhesive containing an isocyanate group-containing urethane prepolymer as a main component. Here, the term "main component" refers to a component that is contained in more than 50% by mass, and preferably more than 70% by mass, of the entire adhesive. The isocyanate group-containing urethane prepolymer is a urethane prepolymer having an isocyanate group at a terminal, which is obtained by reacting one or more polyols having two or more hydroxyl groups in the molecule with one or more polyisocyanates having two or more isocyanate groups in the molecule. The preferred mass average molecular weight of the urethane prepolymer is 2000 to 50000. One or more types of the urethane prepolymer can be used.
[0018] 1.1. Polyols The polyol used as the raw material of the urethane prepolymer has two or more, preferably five or less, hydroxyl groups in the molecule, and any known polyol can be used. Preferred specific examples are shown below.
[0019] 1.1.1. Polyester polyol The polyester polyol is obtained by random co-condensation polymerization of one or more polycarboxylic acids and one or more polyols. Preferred polycarboxylic acids have two or more carboxyl groups in the molecule and have a carbon number of 4 to 24. Specific examples include succinic acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, dodecanedioic acid, eicosanedioic acid, ε-caprolactone, terephthalic acid, isophthalic acid, phthalic anhydride, 2,6-naphthalenedicarboxylic acid, trimellitic acid, and paraoxybenzoic acid. A preferred polyol has two or more hydroxyl groups in the molecule and has a mass average molecular weight of 60 to 5000. Specific examples include ethylene glycol, propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, diethylene glycol, neopentyl glycol, polyethylene glycol, polypropylene glycol, polytetramethylene glycol, 1,4-cyclohexanedimethanol, trimethylolpropane, pentaerythritol, and 1,2,6-hexanetriol.
[0020] 1.1.2. Polyether polyols The polyether polyol has one or more ether bonds in the molecule, and the preferred polyether polyol has a mass average molecular weight of 200 to 10000. Specific examples include polyethylene glycol, polypropylene glycol, and polytetramethylene glycol.
[0021] 1.1.3. Polyolefin polyols Polyolefin polyol has a polyolefin skeleton in the molecule, and preferred polyolefin polyols have a mass average molecular weight of 200 to 10000. Specific examples include hydrogenated polyalkylene polyols such as hydrogenated polybutadiene polyol and hydrogenated polyisoprene polyol, and copolymers of α-olefins.
[0022] 1.1.4. Other polyols Examples of the polyalkylene polyols include polybutadiene polyol and polyisoprene polyol, and polycarbonate polyol.
[0023] 1.2. Polyisocyanates The polyisocyanate which is the raw material of the urethane prepolymer has two or more isocyanate groups in the molecule, and any known polyisocyanate can be used. Specific examples include p-phenylene diisocyanate, 4,4'-diphenylmethane diisocyanate, tolylene diisocyanate, 4,4'-diphenylene diisocyanate, 1,5-octylene diisocyanate, trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, pentamethylene diisocyanate, 1,3-cyclopentane diisocyanate, 1,4-cyclohexane diisocyanate, 4,4'-methylenebis(cyclohexyl isocyanate), methyl 2,4-cyclohexane diisocyanate, methyl 2,6-cyclohexane diisocyanate, diphenylmethane diisocyanate, 1,4-bis(isocyanatemethyl)cyclohexane, 1,3-bis(isocyanatemethyl)cyclohexane, isophorone diisocyanate, and carbodiimide-modified 4,4'-diphenylmethane diisocyanate.
[0024] In the production of the urethane prepolymer of the present invention, the ratio of the amount of polyisocyanate charged to the amount of polyol is preferably 1-5, more preferably 1.5-3, in terms of the equivalent ratio of isocyanate groups / hydroxyl groups.
[0025] 1.3.Other Compounds By incorporating a silane coupling agent into the adhesive of the present invention, the adhesive's adhesion to weatherstrip substrates is improved, and when used for flocked weatherstrips, the water resistance and sliding resistance of the weatherstrip can be improved. Examples of preferred silane coupling agents include γ-glycidoxypropyltrimethoxysilane, γ-glycidoxytriethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, γ-mercaptopropyltrimethoxysilane, vinyltriethoxysilane, vinyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, and γ-methacryloxypropyl-tri(β-methoxyethoxy)silane, etc. Among these, epoxy group-containing organic alkoxysilanes are particularly preferred. The preferred content of the silane coupling agent used in the present invention is 1% by mass or more and 20% by mass or less of the total amount of the adhesive. At 1% by mass or more, sufficient water resistance can be obtained, and at 20% by mass or less, stability after mixing is obtained, and there is little vapor odor of the silane coupling agent when heated and melted, which is unlikely to lead to deterioration of the working environment.
[0026] To the adhesive of the present invention, a catalyst such as a tertiary amine or tin catalyst for increasing moisture reactivity, a tackifier, a filler, a plasticizer, a wax, a stabilizer, an antioxidant, or the like may be added as necessary.
[0027] 1.4. Melting point of adhesive Since urethane prepolymers, which have a melting point, become crystalline solids at temperatures below the melting point, they have the characteristic that when they change from a molten state to a solid state, the viscosity of the resin increases rapidly at the melting point. Therefore, by implanting the pile when the adhesive layer applied to the substrate is in a molten state and then cooling and solidifying the adhesive, the adhesive crystallizes and the pile is firmly fixed to the adhesive layer, making it easy to obtain an initial pile standing strength that can withstand the pinching stress when cutting. Specifically, it is preferable to set the melting point of the adhesive to 40° C. or higher, since the adhesive is solid under normal conditions and can obtain initial nap strength due to the cohesive force during crystallization. If the melting point is less than 40° C., the adhesive cannot obtain initial nap strength under normal conditions and is deformed when clamped, so both ends must be cut, which may result in loss. Moreover, it is preferable that the melting point of the adhesive is 150° C. or less, since this does not affect the weather strip base material and requires less energy for heating. The melting point was measured using a differential scanning calorimeter (DSC214Polyma manufactured by NETZSCH) by heating from 0° C. at a temperature increase rate of 10° C. / min.
[0028] 1.5. Storage modulus of adhesive When the adhesive has cooled and solidified, polymer cross-linking due to moisture curing has not progressed, so the adhesive resin tends to be brittle and may crack when subjected to bending stress. The adhesive, after cooling and solidifying, had a storage modulus of 2.85 x 10 at 25°C before moisture curing. 8 By adjusting the hot melt adhesive to a urethane prepolymer with a modulus of elasticity of 0.1 Pa or less, the adhesive layer will not crack even if a bending stress is applied immediately after the adhesive has cooled and solidified. The preferred range of the storage modulus is 1.00×10 8 Pa or more 2.80×10 8 Pa or less. The storage modulus was measured using a sample having a length of 45 mm, a width of 5 mm and a thickness of 1 mm, which was prepared by pouring the adhesive, which had been heated and melted at 120°C, into a Teflon (registered trademark) mold and pressing it for 15 minutes using a cold press in which room temperature water was poured, using a viscoelasticity measuring device (DMA7100, manufactured by Hitachi High-Tech Science Corporation) at a frequency of 1 Hz and a heating rate of 2°C / min.
[0029] 1.6. Bending fracture strain of adhesive In order to solve the problem that the adhesive resin will crack when subjected to bending stress when cooled and solidified, it is more preferable to use a hot melt adhesive made of a urethane prepolymer that has a bending fracture strain of 1.7% or more at 25°C when cooled and solidified and before moisture curing. By using such an adhesive, the effect of suppressing cracks in the adhesive layer is increased even if bending stress is applied immediately after cooling and solidifying. The bending fracture strain is preferably in the range of 1.9% or more. The bending fracture strain was measured in accordance with JIS K7171 using a tensile tester (Strograph V20-C, Toyo Seiki Seisakusho Co., Ltd.) using a sample with a length of 80 mm, width of 10 mm, and thickness of 4 mm prepared by the same molding method as in the storage modulus measurement.
[0030] 1.7. Dielectric constant of adhesive The adhesive of the present invention has excellent nap raising properties when it has a high dielectric constant. Specifically, when the adhesive resin has a relative dielectric constant of 3 or more and 10 or less, more preferably 3.2 or more and 9 or less, excellent nap raising properties without a shiny appearance can be obtained. When the relative dielectric constant is less than 3, the flocking rate is low and the flocking may lack sliding resistance. The dielectric constant of the adhesive was measured using a precision impedance analyzer (4294A, manufactured by Keysight Technologies, Inc.) at a frequency of 1 MHz in an atmosphere of 23°C and 50% relative humidity on the adhesive before it was moisture-cured.
[0031] 1.8. Tack-free time of adhesive The tack-free time of the adhesive of the present invention is preferably within 10 minutes, more preferably within 5 minutes, and even more preferably from 30 seconds to 4 minutes. When the tack-free time is within the upper limit, the adhesive is easily cooled and solidified during the manufacturing process, and the fibers are prevented from collapsing during post-processing. When the tack-free time is above the lower limit, the fibers are sufficiently implanted. The tack-free time can be measured by the following method. That is, the adhesive that has been heated and melted to 120±5°C is applied uniformly to a thickness of 100±10μm in a 1cm x 1cm square on a 100μm thick polyethylene terephthalate film, and then it is immediately placed in a thermostatic chamber maintained at 25±1°C.The applied surface is then touched with a finger to measure the time until the adhesive loses its tackiness.
[0032] 1.9.Melt Viscosity of Adhesive The adhesive of the present invention preferably has a melt viscosity of 200 to 100,000 mPa·s / 120° C., more preferably 1,000 to 50,000 mPa·s / 120° C., and even more preferably 1,000 to 20,000 mPa·s / 120° C. A melt viscosity below the upper limit makes it easy to apply the adhesive uniformly to the flocked surface of the weatherstrip. The melt viscosity can be easily measured by a BM type viscometer.
[0033] 2. Flocked weather strip A flocked weather strip can be obtained by flocking a substrate with the adhesive of the present invention. The weather strip of the present invention has excellent water resistance and abrasion resistance because the pile is firmly fixed to the substrate by the adhesive of the present invention.
[0034] 3. Manufacturing method of flocked weather strip The heated and melted moisture-curing reactive hot melt adhesive is applied to the sliding surface of the weatherstrip substrate with a thickness of 40 to 150 μm using a roll coater or the like, then the pile is electrostatically flocked to the weatherstrip substrate in a flocking process, the moisture-curing reactive hot melt adhesive is cooled and solidified to fix the pile, and at the same time, the tack on the adhesive surface is eliminated, and then a process of cutting to a specified size is included to complete the flocked weatherstrip. If the adhesive coating thickness is 40 μm or more, sufficient interlocking strength between the pile and the adhesive layer can be obtained, and if it is 150 μm or less, it does not take time to cool and solidify, so the line is short and the line space equipment investment costs are low. EXAMPLES
[0035] The present invention will be described in more detail below with reference to examples and comparative examples. Note that the respective property values of the melting point, storage modulus, dielectric constant, tack-free time and melt viscosity of the adhesive in each example and comparative example were values measured by the methods described above. Furthermore, the adhesives in each of the Examples and Comparative Examples were evaluated for "bending workability of the cured adhesive" and "flockability" by the following methods.
[0036] (Bending workability of cured adhesive) The adhesive is heated to 120°C and melted, then applied to a 1mm thick soft PVC sheet with a roll coater to a thickness of 150μm. The test piece is then immersed in a water tank containing 10°C water for 1 minute to allow the adhesive to cool and solidify, after which it is removed from the water tank and left to stand at 25°C for 5 minutes. The test piece is then bent 90 degrees so that the adhesive layer is on the outside, and the adhesive layer is visually inspected for cracks. If no cracks were found, the rating was "O". If cracks less than 1 mm in length were found, the rating was "△". If cracks 1 mm or longer in length were found, the rating was "X". If the cracks progressed to the point where part of the adhesive layer peeled off, the rating was "XX".
[0037] (Hair transplantability) The adhesive is heated to 120℃ to melt it, and applied to the sliding surface of the weatherstrip part of a 1mm thick soft PVC sheet (weatherstrip base material) with a roll coater to a thickness of 100μm. The pile is immediately electrostatically planted to obtain a test piece. Two minutes after application, the pile standing property is checked by finger pressure. After aging the test piece at 25°C and 50% humidity for 48 hours, the test piece is rubbed with a fingernail to check whether the pile peels off or not, and the wear resistance is confirmed. If the nap-raising property and the sliding resistance were confirmed, the rating was "◯", and if either was not confirmed, the rating was "×".
[0038] Example 1 As the polyester polyol, 40 parts by mass of HS2H-201AP (product name of Toyokuni Oil Mills, Ltd.), 40 parts by mass of HS2H-200S (product name of Toyokuni Oil Mills, Ltd.), and 20 parts by mass of HS2F-305S (product name of Toyokuni Oil Mills, Ltd.) were used and reacted with 23 parts by mass of Sumidur 44S (product name of Sumika Covestro Urethane Co., Ltd.) as the polyisocyanate to obtain an isocyanate-terminated polyurethane hot melt adhesive. The melting point of the adhesive is 59°C, and the storage modulus at 25°C before moisture curing is 1.68×10 8 The dielectric constant of the adhesive was 4.1, the tack-free time was 1 minute 10 seconds, and the melt viscosity was 5450 mPa·s / 120°C. A bending test was carried out on this adhesive, and no cracks were observed in the adhesive layer. The flocking properties of this adhesive were measured and found to be good.
[0039] Comparative Example 1 An isocyanate-terminated polyurethane hot melt adhesive was obtained by reacting 100 parts by mass of HS2H-201AP (a product name of Toyokuni Oil Co., Ltd.) as a polyester polyol with 25 parts by mass of Sumidur 44S (a product name of Sumika Covestro Urethane Co., Ltd.) as a polyisocyanate. The melting point of the adhesive is 51°C, and the storage modulus at 25°C before moisture curing is 2.96×10 8 The dielectric constant of the adhesive was 3.7, the tack-free time was 1 minute 20 seconds, and the melt viscosity was 4500 mPa·s / 120°C. When this adhesive was subjected to a bending test, cracks were found in the adhesive layer. On the other hand, when the hair transplantability was checked, it was found to be good.
[0040] Examples 2 to 5, Comparative Example 2 An isocyanate-terminated polyurethane hot melt adhesive was obtained with the composition shown in Table 1. The melting point, storage modulus at 25° C., bending strain at break, dielectric constant, tack-free time and melt viscosity of these adhesives were measured and are shown in Table 1. Next, the bending workability and flocking property of these adhesives were evaluated in the same manner as in Example 1, and the results are shown in Table 1.
[0041] [Table 1]
[0042] In Table 1, HS2H-351A, HS2F-136P, and HS2F-231AS represent polyester polyols manufactured by Toyokuni Oil Mills, P-2011 represents polyester polyol manufactured by Kuraray Co., Ltd., and PTMG-3000 represents polytetramethylene ether glycol (polyether polyol).
Claims
1. The main component is an isocyanate group-containing urethane prepolymer, the melting point is 40° C. or more and 150° C. or less, and the storage modulus at 25° C. before moisture curing is 1.00×10 8 Pa or more and 2.85×10 8 The moisture-curing reactive hot melt adhesive for flocking weather strips is characterized by having a viscosity of 0.01 Pa or less.
2. A moisture-curing reactive hot melt adhesive for weatherstrip flocking as described in claim 1, having a tack-free time of 5 minutes or less as measured by the following test method. (Test method): The adhesive is heated and melted to 120±5° C. and applied uniformly to a thickness of 100±10 μm in a 1 cm×1 cm square on a 100 μm thick polyethylene terephthalate film, and the film is immediately placed in a thermostatic chamber maintained at 25±1° C. The applied surface is then touched with a finger to measure the time until the adhesive loses its tackiness.
3. A moisture-curing reactive hot melt adhesive for weatherstrip flocking as described in claim 1 or claim 2, wherein the isocyanate group-containing urethane prepolymer is obtained by reacting a polyol with a polyisocyanate, and the polyol includes a polyester polyol.
4. A moisture-curing reactive hot melt adhesive for weatherstrip flocking as described in claim 3, wherein the polyester polyol consists of at least two types of polyester polyol.
5. 5. The moisture-curing reactive hot melt adhesive for flocking weather strips according to claim 1, characterized in that the bending fracture strain at 25°C before moisture curing is 1.7% or more.
6. 6. The moisture-curable reactive hot melt adhesive for flocking weather strips according to claim 1, wherein the adhesive has a relative dielectric constant at 25° C. of 3 or more and 10 or less.
7. The moisture-curable reactive hot melt adhesive for flocking weather strips according to any one of claims 1 to 6, characterized in that the melt viscosity is 1,000 to 50,000 mPa·s / 120°C.
8. A flocked weatherstrip, comprising a substrate and flocked thereon via the moisture-curable reactive hot melt adhesive for flocking weatherstrips according to any one of claims 1 to 7.
9. A method for producing a flocked weatherstrip, comprising the steps of heating and melting the moisture-curing reactive hot melt adhesive for flocking weatherstrips according to any one of claims 1 to 8, applying the adhesive to a substrate in a thickness of 40 to 150 μm, electrostatically flocking pile fibers onto the substrate, cooling and solidifying the adhesive to adhere the pile fibers to the substrate, and then cutting the substrate to a predetermined size.
Citation Information
Patent Citations
Moisture-curing type reactive hot-melt adhesive for weatherstrip filling, weatherstrip with filling and method for producing the same
JP2002038120A
Method of manufacturing flocked product for automobile
JP2002224612A
Adhesive useful for attaching a vehicle window
JP2016508170A